Desert power 2050: Regional and sectoral impacts of renewable electricity production in Europe, the Middle East and North Africa - Alvaro Calzadilla; Manfred Wiebelt; Julian Blohmke; Gernot Klepper (Kiel Institute for the World Economy (IfW), 2014)
'Desert Power 2050' is probably the world's most ambitious strategy report towards the decarbonization of the power sector in Europe, the Middle East and North Africa (EUMENA). The report inspired by the Desertec vision aims at providing clean energy from MENA's desert regions to the entire MENA region as well as exporting electricity to Europe. The report shows that an integrated EUMENA power system based on more than 90 percent renewables is technically feasible and economically viable. We use a combination of a global general equilibrium model (DART) and a multiplier analysis to evaluate the economic effects behind 'Desert Power 2050' from a broader perspective, including not only the energy activities but also the repercussions in other sectors of the economies. The results show that the extent of the costs and benefits for both regions depend on the type of strategy adopted to finance the build-up of the power plants and the expected development of the levelised cost of electricity for the different technologies. Furthermore, the viability of a transition towards renewable energy as proposed by 'Desert Power 2050' depends to a great extent on the international climate policy.
Keywords: C68; C67; Q42; Q58; O52; O55; 330; Computable General Equilibrium; Multiplier Analysis; Renewable Energy; Climate Policy; Europe-North Africa-the Middle East